Development of a Teacher Guideline for Wisdom Education Management in Teaching and Learning in Yunnan’s Secondary Schools - Xuan Wang; Panchit Longpradit (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The purposes of this study were to survey current situations of teachers on wisdom education in teaching and learning in secondary schools in Yunnan, China, and to propose a teacher guideline for wisdom education in teaching and learning and evaluate its effectiveness in view of experts. This research adopted two sets of questionnaires of quantitative methodology as data collection methods, one was for surveying 100 secondary school teachers in terms of wisdom education teaching and learning preparation ability, wisdom education teaching and learning implementation ability, wisdom education teaching and learning evaluation reflection ability, wisdom education teaching and learning innovation ability; and another was for verifying the effectiveness of the proposed guideline by views of 5 experts based on the criteria of 4 abilities, including the preparation, implementation, evaluation reflection and innovation abilities of wisdom education in teaching and learning. Firstly, the survey results showed that the overall four components of wisdom education in teaching and learning was at a high level with the mean score of 3.96. Secondly, the expert reviews showed that the effectiveness of the wisdom education guideline for teachers in teaching and learning was very positive and enlightening.